Effect of foliar nutrients application to the growth and yield of Physalis peruviana and Physalis alkekengi. Issue 1 (1st February 2022) - Sholehah, Diana Nurus; Ermavitalini, Dini; Khasanah, Miratul; Utami, Edy Setiti Wida; Purnobasuki, Hery
Abstract: Physalis Sp. is a potential medicinal plant and functional food. The use of appropriate nutrients can gain optimal plant growth and productivity. This study aimed to determine the macro and micronutrients that can provide optimal growth and yield of Physalis sp. This research was conducted at a greenhouse in Bangkalan Madura. A factorial randomized block design with four replications was used in this study. The first factor was the species of Physalis Sp., namely P. peruviana and P. alkekengi . The second factor is nutrition at four levels: a spray of water only as control; foliar application of macronutrients at a dose of 2 g/L; foliar application of micronutrients at a dose of 0, 125 g/L; foliar Application of a combination of macronutrients 1 g/L and micronutrients 0, 0625 g/L. The data obtained were analyzed using analysis of variance (ANOVA) followed by Least Significant Difference (LSD) at the 5 % level. Nutrition significantly affected growth (plant height, stem diameter, and number of leaves) and yield (number of fruit). The interaction between treatments occurred in the number of fruits. Micronutrients gave the highest number of fruit, both species of Physalis sp.